1995
DOI: 10.1083/jcb.131.2.339
|View full text |Cite
|
Sign up to set email alerts
|

Envelope glycoprotein interactions in coronavirus assembly.

Abstract: Abstract. Coronaviruses are assembled by budding into smooth membranes of the intermediate ERto-Golgi compartment. We have studied the association of the viral membrane glycoproteins M and S in the formation of the virion envelope. Using coimmunoprecipitation analysis we demonstrated that the M and S proteins of mouse hepatitis virus (MHV) interact specifically forming heteromultimeric complexes in infected cells. These could be detected only when the detergents used for their solubilization from cells or viri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
156
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(169 citation statements)
references
References 46 publications
12
156
0
1
Order By: Relevance
“…We and others have shown earlier that budding of coronaviruses occurs at these particular membranes (18,21,45,46). The reasons for this have so far remained obscure because neither of the major viral envelope proteins was found to localize to these membranes (20,29). If the E protein by itself indeed localizes to pre-Golgi membranes, this would most likely provide the explanation.…”
Section: Discussionmentioning
confidence: 93%
“…We and others have shown earlier that budding of coronaviruses occurs at these particular membranes (18,21,45,46). The reasons for this have so far remained obscure because neither of the major viral envelope proteins was found to localize to these membranes (20,29). If the E protein by itself indeed localizes to pre-Golgi membranes, this would most likely provide the explanation.…”
Section: Discussionmentioning
confidence: 93%
“…It will thus be important to understand the basis of its selective inclusion into particles, and, conversely, the reason why other proteins are excluded. It has been previously shown that there are specific associations between the M and S proteins while M is coalescing into higher-order arrays, and these may be key to recruiting S into budding viral particles (36,38,39). However, much remains to be learned of the molecular details of this process, and an active role for E protein cannot be ruled out.…”
Section: Discussionmentioning
confidence: 97%
“…in the endoplasmic reticulum (36,38,39). S multimers must somehow fit specifically into the interstices of the arrays of M (or M and E) monomers without contributing much to their overall stability.…”
mentioning
confidence: 99%
“…They are trimeric type I integral membrane proteins, organized into subdomains necessary for receptor engagement (S1) and membrane fusion (S2) (20). S has been shown to be incorporated into virions by interactions with M (45,51,52). In infected cells and in S-transfected cells, S can be transported to the cell surface, where it mediates fusion with adjoining cells, resulting in the formation of syncytia (2,11,39).…”
mentioning
confidence: 99%